Differences in initial stroke severity between Mexican Americans and non-Hispanic whites vary by age: the Brain Attack Surveillance in Corpus Christi (BASIC) project - Wing, Jeffrey J. (Cerebrovasc Dis, 2014)
BACKGROUND: A wide variety of racial and ethnic disparities in stroke epidemiology and treatment have been reported. Race-ethnic differences in initial stroke severity may be one important determinant of differences in outcome after stroke. The overall goal of this study was to move beyond ethnic comparisons in the mean or median severity, and instead investigate ethnic differences in the entire distribution of initial stroke severity. Additionally, we investigated whether age modifies the relationship between ethnicity and initial stroke severity as this may be an important determinant of racial differences in outcome after stroke. METHODS: Ischemic stroke cases were identified from the population-based Brain Attack Surveillance in Corpus Christi (BASIC) project. National Institutes of Health Stroke Scale (NIHSS) was determined from the medical record or abstracted from the chart. Ethnicity was reported as Mexican American (MA) or non-Hispanic white (NHW). Quantile regression was used to model the distribution of NIHSS score by age category (45–59, 60–74, 75+) to test whether ethnic differences exist over different quantiles of NIHSS (5 percentile increments). Crude models examined the interaction between age category and ethnicity; models were then adjusted for history of stroke/transient ischemic attack, hypertension, atrial fibrillation, coronary artery disease, and diabetes. Results were adjusted for multiple comparisons. RESULTS: There were 4,366 ischemic strokes, with median age 72 years (IQR: 61–81), 55% MA and median NIHSS of 4 (IQR: 2–8). MAs were younger, more likely to have a history of hypertension and diabetes, but less likely to have atrial fibrillation compared to NHWs. In the crude model, the ethnicity-age interaction was not statistically significant. After adjustment, the ethnicity-age interaction became significant at the 85(th) and 95(th) percentiles of NIHSS distribution. MAs in the younger age category (45–59) were significantly less severe by 3 and 6 points on the initial NIHSS than NHWs, at the 85(th) and 95(th) percentiles, respectively. However, in the older age category (75+), there was a reversal of this pattern; MAs had more severe strokes than NHWs by about 2 points, though not reaching statistical significance. CONCLUSIONS: There was no overall ethnic difference in stroke severity by age in our crude model. However, several potentially important ethnic differences among individuals with the most severe strokes were seen in younger and older stroke patients that were not explained by traditional risk factors. Age should be considered in future studies when looking at the complex distributional relationship between ethnicity and stroke severity.